2008
DOI: 10.1007/s11571-008-9040-6
|View full text |Cite
|
Sign up to set email alerts
|

Consciousness related neural events viewed as brain state space transitions

Abstract: This theoretical and speculative essay addresses a categorical distinction between neural events of sensory-motor cognition and those presumably associated with consciousness. It proposes to view this distinction in the framework of the branch of Statistical Physics currently referred to as Modern Critical Theory (Stanley, Introduction to phase transitions and critical phenomena, 1987; Marro and Dickman, Nonequilibrium phase transitions in lattice, 1999). Based on established landmarks of brain dynamics, netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 175 publications
(128 reference statements)
1
19
0
1
Order By: Relevance
“…Another fundamental postulate is that consciousness occurs in the brain in the dynamic regime of self-organized criticality (Werner, 2009a) often indicated by power–law relationships (Bak and Paczuski, 1995; Beggs and Plenz, 2003) although not without critique (Beggs and Timme, 2012). However, power–laws of neuronal population events are also present in anesthetized animals and in vitro preparations (Massobrio et al, 2015) and systematic assessment their state-dependence has been scarce (Ribeiro et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another fundamental postulate is that consciousness occurs in the brain in the dynamic regime of self-organized criticality (Werner, 2009a) often indicated by power–law relationships (Bak and Paczuski, 1995; Beggs and Plenz, 2003) although not without critique (Beggs and Timme, 2012). However, power–laws of neuronal population events are also present in anesthetized animals and in vitro preparations (Massobrio et al, 2015) and systematic assessment their state-dependence has been scarce (Ribeiro et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…During spontaneous ongoing activity, neuronal population firing is closely correlated with the negative phase of the LFP, mainly due to synchronous dendritic depolarization of the population at a time scale that corresponds to the integration time of neurons – approximately 10 ms (Gabernet et al, 2005). The negative phases of LFPs (nLFPs) form spatiotemporal patterns whose size distribution follows scale-free (power–law) distribution (Beggs and Plenz, 2003), suggesting the presence of self-organized criticality (Werner, 2009a). The diversity of nLFP patterns serves as a measure of the brain’s state repertoire that may, in turn, correlate with the state of consciousness.…”
Section: Introductionmentioning
confidence: 99%
“…In the insightful moment when subjects perceive Mooney faces, neural synchronization spreads all over the brain, which lasts for about 100 ms (Rodriguez et al 1999). Such synchronization is thought to be related to some of the Gestalt rules and feature binding (Singer 2009) or a mechanism for transient functional neurocognitive connectivity (Werner 2009). In general, when ''Mooney'' objects (i.e., bi-level quantized images of various objects) and their original grayscale photographs are presented alternately, activities of inferior temporal and parietal regions are enhanced (Dolan et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that dynamical patterns of these correlations are shaped by a complex interplay between underlying anatomical connections and ongoing activity of the interacting regions . Thus, allowing for long-distance co-activity of functionally segregated brain areas and forming the basis of cognitive functions (Werner 2009). However, the exact mechanisms contributing to the longrange cortical interactions still remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%